The Effect of Drying Method on Potential Antioxidants in Ethanol Extract of Sungkai Leaf (Parenoma Canescens Jack.) Simplicia from Kalimantan - Fahrina Kasuma Wati; Siti Hasnah - Hasnah (Program Studi Kimia, Universitas Lambung Mangkurat, 2022)
Sungkai (P. canescens) is a medicinal plant whose leaves are used to alleviate fever and strengthen the body's immune system. This study aimed to determine the effect of the simplicia drying technique on the antioxidant potential of the ethanol extract of Sungkai leaves from Kalimantan. The drying method employed was oven drying at 70°C, oven drying at 50°C, sun drying, and wind drying. The study's findings indicated that the antioxidant activity of all drying techniques was in the very active category. The drying method with the lowest antioxidant potential was oven drying at 50°C with IC50 value of 13.340 ppm, wind drying with IC50 value of 14.610 ppm, sun drying with IC50 value of 16.799ppm, and oven drying at 70°C with IC50 value of 17.034 ppm. Keywords: Sungkai leaf ; IC50; antioxidant